TRANSFORMASI DIGITAL UMKM MELALUI QRIS DAN SIAPIK DI DESA DUKUH DEMPOK KECAMATAN WULUHAN KABUPATEN JEMBER - Yani Dahliani; Ainun Najib; Yudhi Eka Hanafi; Sugiyono, Sugiyono (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The phenomenon of global technological advancements has brought significant changes to the business sector. It is undeniable that significant changes have occurred in Indonesia, including in the micro, small, and medium enterprises (MSMEs) sector. Although most MSMEs are adept at using mobile phones, many still haven't fully utilized digital technology. This is evident in the fact that many businesses still haven't used digital payments (QRIS) and financial record-keeping systems like SIAPIK. This activity aims to improve the understanding and skills of business owners (MSMEs) in using Qris as a payment transaction method and digital financial recording using the Siapik application. This activity was held for 10 days, starting from August 4 to August 14, 2025, involving 15 MSME business actors in Dukuh Dempok village. This activity used an observation method with direct interviews with business actors in the market and roadside areas in Dukuh Dempok village, Ambulu sub-district, Jember Regency from August 4-10, 2025, training and socialization were carried out at the Gumuk Watu educational tour on August 11, and after the training and socialization until August 14, an evaluation was conducted to see how business actors used the 2 digital-based technologies. The results turned out to be satisfactory considering that participants or MSME business actors succeeded in using Qris and Siapik. Data shows a 90% adoption rate. However, challenges such as the continued predominance of cash usage among customers and the lack of consistency among business owners in using digital financial accounting applications need to be addressed through continued mentoring. Face-to-face approaches with hands-on practice have proven effective in encouraging MSMEs to adopt these applications